Ultraviolet/blue light emitting high-quality graphene quantum dots and their biocompatibility. (December 2020) - Lee, Na Eun; Jeong, Jong-Min; Lim, Hyung San; Lee, Sang Yoon; Cho, Sung Oh
Abstract: Fluorescent graphene quantum dots (GQDs) have a significant potential in the application to bio-fields. However, most of the GQDs synthesized by existing methods face limitations due to the harmful chemicals involved in their synthesis and the presence of various oxygen functional groups, both of which affect the biocompatibility of the GQDs. Here, we present a simple approach to fabricating fluorescent and biocompatible high-quality GQDs with low oxygen content without the involvement of harmful chemicals. High-quality GQDs are synthesized by hydrogen-assisted pyrolysis of silicon carbide and this dry synthesis process allows the GQDs to possess high crystallinity with no unwanted chemicals on the surface. Subsequently, the high-quality GQDs are slightly oxidized through sonication in ethanol, but the treated GQDs (t-GQDs) still retain their high crystallinity. The t-GQDs exhibit strong ultraviolet/blue light emission with a high yield of 30.9%, a phenomenon that can be attributed to intrinsic emission resulting from the low oxygen content of the t-GQDs. Furthermore, the t-GQDs show low cytotoxicity even at a high concentration of 200 μg/mL due to the absence of harmful chemicals during their synthesis and the low oxygen content of the t-GQDs. These results demonstrate the excellence of the t-GQDs and their applicability in bio-fields. Graphical abstract: Image 1